Statistical Similarity Analysis Based on Neutrosophic Interval Probability - Jiaming Song; Rui Yong; Yingying Zhang; Minna Xu; Jun Ye (Neutrosophic Sets and Systems, 2021)
The roughness of the rock joints has a significant influence on the mechanical properties and deformation behavior of the rock masses. Due to the significant heterogeneity of the surface roughness of rock joints, there may be considerable variabilities, which makes it difficult to accurately determine the roughness. The evaluation of the anisotropic characteristics of joint roughness based on classical probability and statistics cannot reflect the vague, incomplete, imprecise, and indeterminate information of the roughness in different orientations. In this original study, we first propose the generalized Dice similarity measures based on neutrosophic interval statistical number (NISN) for evaluating the similarity of the roughness in different orientations. This method was applied to determine the similarity between the roughness along the sliding direction and each measurement direction. The research results show that this method can effectively determine the similarity between the roughness in different orientations. It may help determine the roughness along the potential sliding direction based on the roughness obtained in the direction with better measurement conditions.